A Numerical Study on the Effects of Laser Refractive Surgery: SMILE vs PRK - Fantaci, Benedetta; Caruso, Gaia; Calvo, Begoña (Jornada de Jóvenes Investigadores del I3A, 2023)
In the last two decades, corneal laser surgery has become a common procedure to correct medium-low refractive defects. It consists of reshaping the corneal geometry by means of a laser in order to correct the present refractive error. In this work, we compare the opto-mechanical performance of two laser surgery procedures: Photorefractive Keratectomy (PRK) and Small Incision Lenticule Extraction (SMILE).